Relationship of Level of Knowledge of Plywood Factory Employees about Dangers of Lung Disease Due to Work With use of Self Protection Tools - Bayu Azhar; Siti Siti Ramalia; Veny Elita (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
The industrial sector becomes a job that requires a lot of human resources, developing industries can give negative results such as air pollution by dust arising from industrial processing. This study discusses the level of knowledge of plywood factory employees about the dangers of occupational diseases with the use of personal protective equipment. This data collection uses questionnaires and collection sheets. The design of this study used a descriptive research design with the study "Cross sectional study". The study was conducted on 95 respondents at Asia Citra Factory in Tanjung Melawan Tanah Putih Subdistrict used the cluster sampling technique. The analysis used was the Chi-square test. The results of this study indicate there is no relationship between the level of knowledge of plywood factory employees about the dangers of occupational diseases and the use of personal protective equipment (p value 0.91> 0.05).